Plummer-Vinson syndrome and dilation therapy: A report of two cases - Fikret DEMİRCİ and M. Cemil SAVAŞ and Necip KEPKEP and Vahap OKAN and Mehmet YILMAZ and Mehmet BÜYÜKBERBER and M. Taner GÜLŞEN (Turkish Journal of Gastroenterology, 2019)
-